Lactose intolerance and levothyroxine malabsorption: a review of the literature and report of a series of patients treated with liquid L-T4 without lactose - Ferrari, Silvia Martina; Patrizio, Armando; Mazzi, Valeria; Ragusa, Francesca; Botrini, Chiara; Elia, Giusy; Balestri, Eugenia; Barozzi, Emilio; Rugani, Licia; Bracchitta, Fabiana; Stoppini, Giulio; Frenzilli, Giada; et al. (Frontiers in Endocrinology, 2024)
In hypothyroid patients needing large doses of levothyroxine (L-T4) (> 1.7-2 mcg/kg/day) to reach euthyroidism, lactose intolerance (LI) needs to be excluded, owing to the high prevalence in the population. If LI is present, a lactose-free diet decreases the rate of L-T4 malabsorption. However, an increased requirement of L-T4 is described in patients with LI, that can be beneficially treated using lactose-free L-T4 formulation. The lactose-free liquid L-T4 formulation is able to circumvent LI malabsorption leading to the normalization of TSH in patients with subclinical hypothyroidism, and long term stable thyroid-stimulating hormone (TSH) levels.